Are "Associate Professors" Better Than "Associate Teaching Professors"? Student and Faculty Perceptions of Faculty Titles. (January 2020) - Morling, Beth; Lee, Jeong Min
Full-time teaching-focused faculty at research universities may hold alternative titles such as Assistant Teaching Professor, Instructor, or Lecturer. We manipulated the title of a fictitious faculty target to investigate how such titles are perceived. Student and lay respondents ( N = 317) respected and liked all targets, and their ratings did not differ depending on title. Faculty respondents ( N = 645) also liked and respected all the targets but predicted that Associate Teaching Professors, compared to Associate Professors, would be paid less and would be less likely to have tenure, hold the PhD, or be respected outside their university. Lecturer and Instructor titles were estimated to be even lower in status. We discuss what our data indicate about the status of teaching in academia.